NUMERICAL SIMULATION OF FRACTURE BEHAVIOR FOR 52 M NICKEL BASE ALLOY DMWJ UNDER DIFFERENT VERTICAL EARTHQUAKE LOADS (MT) - YUAN HongWei; YANG Jie; CUI Wei; CHEN HaoFeng (Jixie qiangdu, 2022)
Nuclear power plants should be strictly protected against earthquakes. Especially in nuclear power pressure vessels, there are a lot of dissimilar metal welded joints（DMWJ）. They are the weak link owing to their highly heterogeneous microstructure; mechanical; thermal; and fracture properties, and some defects that occur at different positions within the DMWJs. To ensure the safety of nuclear power pressure vessels, it is important to examine the fracture behavior of DMWJ in detail. In addition to the earthquake loads, constraint is an important factor affecting the fracture behavior of DMWJ. To understand this behavior, both constraint and earthquake loads must be considered. In this study, taking nuclear safe end DMWJ as the research object, four single edge-notched bend（SENB） specimens with central crack under different constraints were selected. Different vertical earthquake loads under five earthquake intensities and three actual earthquakes were applied to the specimen respectively by mass acceleration application method. The fracture behavior of DMWJ under various vertical earthquake loads and the interaction between vertical earthquake load and constraint were numerically simulated. The results showed that with the increase of earthquake intensity, the J-R curve of DMWJ gradually decreases. In contrast to the DMWJ with high constraint, the decrease of J-R curve of the DMWJ with low constraint is more obvious. It is related to the fracture mode of DMWJ under different constraints. Under the actual earthquake, the change of J-R curve is related not only to the earthquake magnitude, but also to the acceleration time history curve of earthquake wave.